A new species of Ananteris Thorell (Scorpiones: Buthidae) from Colombia - Botero-Trujillo, Ricardo (Zootaxa, 2007)
Ananteris myriamae sp. nov. is described from the department of Meta, Colombia. This species is characterized, among other features, by the presence of two concavities in the anterior margin of the carapace, and six carinae in metasomal segment IV. With its description, the number of known species of Ananteris is raised to 59, five of which are present in Colombia.